Impact of COPD and asthma on in-hospital mortality and management of patients with heart failure in England and Wales: an observational analysis - Claudia Gulea; Rosita Zakeri; Jennifer K Quint; Constantinos Kallis (BMJ Open)
Objective To evaluate the association between having concomitant chronic obstructive pulmonary disease (COPD) or asthma, and in-patient mortality and post-discharge management among patients hospitalised for acute heart failure (HF).Setting Data were obtained from patients enrolled in the National Heart Failure Audit.Participants 217 329 patients hospitalised for HF in England–Wales between March 2012 and 2018.Outcomes In-hospital mortality, referrals to cardiology follow-up and prescriptions for HF medications were compared between patients with comorbid COPD (COPD-HF) or asthma (asthma-HF) versus HF-alone using mixed-effects logistic regression.Results Patients with COPD-HF were more likely to die during hospitalisation, and those with asthma-HF had a reduced likelihood of death, compared with patients who had HF-alone ((adjusted)ORadj, 95% CI: 1.10, 1.06 to 1.14 and ORadj, 95% CI: 0.84, 0.79 to 0.88). In patients who survived to discharge, referral to HF follow-up services differed between groups: patients with COPD-HF had reduced odds of cardiology follow-up (ORadj, 95% CI 0.79, 0.77 to 0.81), while cardiology referral odds for asthma-HF were similar to HF-alone. Overall, proportions of HF medication prescriptions at discharge were low for both COPD-HF and asthma-HF groups, particularly prescriptions for beta-blockers.Conclusions In this nationwide analysis, we showed that COPD and asthma significantly impact the clinical course in patients hospitalised for HF. COPD is associated with higher in-patient mortality and lower cardiology referral odds, while COPD and asthma are both associated with lower use of prognostic HF therapies on discharge. These data highlight therapeutic gaps and a need for better integration of cardiopulmonary services to improve healthcare provision for patients with HF and coexisting respiratory disease.